THE PERCEPTION OF EXTENSIVE READING ON STUDENTS PERFORMANCE IN NARRATIVE TEXT - Al-Fadil, Muhammad Zidane; Afriani, Imro'atul Husna; Mochamad Ardi Setyawan (Universitas PGRI Palembang, 2025)
This study explores students’ perceptions of extensive reading and its impact on their understanding of narrative texts at a vocational high school in Sritanjung, Banyuwangi. Using a quantitative approach, data were gathered through questionnaires, interviews, observations, and documentation involving 10 tenth-grade students. The research aimed to determine how extensive reading influences comprehension of story elements such as structure, characters, and plot. Results show that most students view extensive reading positively, recognizing its contribution to improved reading skills, vocabulary development, and storytelling ability. Notably, 77% of participants expressed favorable perceptions, indicating both linguistic and motivational benefits. The study also found that higher engagement in extensive reading activities is associated with better comprehension and increased motivation. Overall, the extensive reading program is considered effective but still needs further strategies to encourage regular reading habits.